Assessment of the surface reactivity of AA1050 aluminium alloy. (1st May 2013) - Witkowska, Malgorzata; Thompson, George Edward; Hashimoto, Teruo; Koroleva, Elena
<x xml:space="preserve">Abstract</x> During processing from cast slab to thin gauge material, the AA1050 aluminium alloy proceeds through various stages of thermomechanical processing, with the conditions at each processing stage influencing the microstructure of the final coil. The reactivity of the material in defined chemical and electrochemical processes has been demonstrated as a useful method to describe variance in the microstructure and surface chemical properties of the aluminium. Various techniques have been employed to assess the reactivity of the surface, e.g. sodium hydroxide etching and open circuit potential measurements. Etching in hydrochloric acid was also carried out on samples that had been previously alkaline etched. The weight losses in both alkaline and acid solutions were measured, and the surface responses were examined and analysed using scanning electron microscopy and white light interferometry. Visible and measurable differences in the sample surfaces were observed. Finally, the novel state‐of‐the‐art technique of in‐SEM 3D electron tomography was used to characterize the near‐surface microstructure in a way that has not previously been possible for such a representative volume. Copyright © 2013 John Wiley & Sons, Ltd.